Application of the Kvaal method for adult dental age estimation using Cone Beam Computed Tomography (CBCT). (November 2016) - Marroquin Penaloza, Talia Yolanda; Karkhanis, Shalmira; Kvaal, Sigrid Ingeborg; Nurul, Firdaus; Kanagasingam, Shalini; Franklin, Daniel; Vasudavan, Sivabalan; Kruger, Estie; Tennant, Marc
Abstract: Different non-invasive methods have been proposed for dental age estimation in adults, with the Kvaal et al. method as one of the more frequently tested in different populations. The purpose of this study was to apply the Kvaal et al. method for dental age estimation on modern volumetric data from 3D digital systems. To this end, 101 CBCT images from a Malaysian population were used. Fifty-five per cent were female (n = 55), and forty-five percent were male (n = 46), with a median age of 31 years for both sexes. As tomographs allow the observer to obtain a sagittal and coronal view of the teeth, the Kvaal pulp/root width measurements and ratios were calculated in the bucco-lingual and mesio-distal aspects of the tooth. From these data different linear regression models and formulae were built. The most accurate models for estimating age were obtained from a diverse combination of measurements (SEE ±10.58 years), and for the mesio-distal measurements of the central incisor at level A (SEE ±12.84 years). This accuracy, however is outside an acceptable range in for forensic application (SEE ±10.00 years), and is also more time consuming than the original approach based on dental radiographs. Highlights: Application and adaptation of Kvaal et al. method on tomographs. Inclusion of teeth with small fillings in the analysis vs previous studies using only sound teeth. First study applying Kvaal et al. method in a Malaysian population. Odontometric analysis of pulp/tooth width dimensions in coronal and sagittal planes.